바이오센서 세포 제작을 이용한 세포 아데노신 삼인산 방출의 측정 - 손민정(Min-Jeong Son); 레안위(Qui Ahn Le); 김준철(Joon-Chul Kim); 김경희(Kyoung-Hee Kim); 우선희(Sun-Hee Woo) (Yaghag-hoi-ji, 2019)
In this study, we established a biosensor cell that can directly respond to ATP in order to measure ATP release from a single cell in real-time with high time resolution. We made HEK293 cells overexpressing P2X7 purinoceptors, the ATP-gated cation channel, with green fluorescence proteins (GFPs). Overexpression of P2X7 receptors was confirmed by reverse transcription-polymerase chain reaction, immunoblotting method, and fluorescence microscopy. In addition, the overexpression of P2X7 receptors was functionally confirmed by measuring ATP-induced cation current in these cells using whole-cell patch clamp technique. Application of ATP-containing external solutions produced inward currents at −70 mV in P2X7-expressing HEK293 cells, in a concentration-dependent manner with an EC50 of 31.2 µM. Maximal P2X7 inward current (14.2 ± 1.76 pA/pF, n = 10) was observed at about 0.8 mM ATP. ATP-dependent HEK293 cell currents were almost completely blocked by suramin (30 µM), the P2 purinergic antagonist (0.17 ± 0.13 pA/pF, n = 10, p < 0.0001), and they were negligible in the HEK293 cells expressing GFP only (0.28 ± 0.07 pA/pF, n = 11). The ATP-biosensor cells successfully detected ATP release from single atrial myocyte under shear stress at millisecond intervals. This ATP detection method may be used to directly quantify real-time ATP release, which may provide improved spatial and temporal information on cellular ATP release. KCI Citation Count: 0